Respuestas
Respuesta dada por:
11
siendo el término general de la sucesión:
![a_n=3n+1 a_n=3n+1](https://tex.z-dn.net/?f=a_n%3D3n%2B1+)
entonces pará cada término:
![(n=1)\Rightarrow a_1=3+1=4\\ \\ (n=2)\Rightarrow a_2=3(2)+1=7\\ \\ (n=3)\Rightarrow a_3=3(3)+1=10\\ \\ a_4=3(4)+1=13 (n=1)\Rightarrow a_1=3+1=4\\ \\ (n=2)\Rightarrow a_2=3(2)+1=7\\ \\ (n=3)\Rightarrow a_3=3(3)+1=10\\ \\ a_4=3(4)+1=13](https://tex.z-dn.net/?f=%28n%3D1%29%5CRightarrow+a_1%3D3%2B1%3D4%5C%5C+%5C%5C+%28n%3D2%29%5CRightarrow+a_2%3D3%282%29%2B1%3D7%5C%5C+%5C%5C+%28n%3D3%29%5CRightarrow+a_3%3D3%283%29%2B1%3D10%5C%5C+%5C%5C+a_4%3D3%284%29%2B1%3D13)
![(n=5) (n=5)](https://tex.z-dn.net/?f=%28n%3D5%29+)
entonces pará cada término:
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años